A revision of Solanum subsection Lathyrocarpum (the S. carolinense Clade) - Wahlert, Gregory (2015)
A new taxonomic circumscription of Solanum section Lathyrocarpum is proposed to include 11 species from North and South America. The section is placed in the cosmopolitan S. subgenus Leptostemonum, which contains 350?450 species. As defined here, S. sect. Lathyrocarpum includes all the taxa resolved in the Carolinense clade in previous molecular phylogenetic studies as well as one species not sampled in those analyses. The combination of morphological characters that define the group includes: herbaceous perennial habit with extensive root systems, often with endogenous buds that can sprout, a sparse to dense indumentum of sessile to stalked stellate hairs and tapered prickles, 2- to 3-foliate to plurifoliate sympodial units, extra-axillary inflorescences with 1?20 flowers, a weakly andromonoecious reproductive system, corollas ranging in color from white to lavender, and fruits maturing to yellow or yellowish-orange. Most species in the section have a weedy habit and grow in highly disturbed areas, but four are narrowly distributed. One species, S. carolinense, is a noxious invasive weed that has been inadvertently introduced to many areas around the world. There are a variety of ploidy levels represented in the group (n = 12, 18, 24, and 36). In this work, we present a new circumscription of the section and provide descriptions, distribution maps, preliminary IUCN conservation assessments, and a key to identify the 11 included species. We also designate lectotypes for nine names and select a neotype for S. dimidiatum.